2013
DOI: 10.1038/cr.2013.93
|View full text |Cite
|
Sign up to set email alerts
|

Generation of haploid embryonic stem cells from Macaca fascicularis monkey parthenotes

Abstract: Recent success in the derivation of haploid embryonic stem cells (haESCs) from mouse via parthenogenesis and androgenesis has enabled genetic screening in mammalian cells and generation of gene-modified animals. However, whether haESCs can be derived from primates remains unknown. Here, we report the derivation of haESCs from parthenogenetic blastocysts of Macaca fascicularis monkeys. These cells, termed as PG-haESCs, are pluripotent and can differentiate to cells of three embryonic germ layers in vitro or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 48 publications
4
97
0
1
Order By: Relevance
“…The results showed that, as expected, the DMRs of H19 and Meg3 were free of methylation while DMR of Snrpn largely retained methylation in both cell lines ( Figure 1H). Interestingly, different from mouse PG-haESCs, in which, DNA methylation was quickly lost at maternally imprinted loci during haploid ESC derivation and in vitro culture [9], hPGES1 and hPGES2 cells maintained a stable maternal imprinting state in early and late passages (Supplementary information, Figure S5B), consistent with previous observations in monkey PG-haESCs [5]. Finally, we investigated the methylation profile of all genes in haploid cells and control diploid cells by performing whole-genome bisulfite sequencing (WGBS) analysis using DNA samples extracted from the cells that we prepared for RNA-seq analysis.…”
Section: Dear Editorsupporting
confidence: 78%
See 2 more Smart Citations
“…The results showed that, as expected, the DMRs of H19 and Meg3 were free of methylation while DMR of Snrpn largely retained methylation in both cell lines ( Figure 1H). Interestingly, different from mouse PG-haESCs, in which, DNA methylation was quickly lost at maternally imprinted loci during haploid ESC derivation and in vitro culture [9], hPGES1 and hPGES2 cells maintained a stable maternal imprinting state in early and late passages (Supplementary information, Figure S5B), consistent with previous observations in monkey PG-haESCs [5]. Finally, we investigated the methylation profile of all genes in haploid cells and control diploid cells by performing whole-genome bisulfite sequencing (WGBS) analysis using DNA samples extracted from the cells that we prepared for RNA-seq analysis.…”
Section: Dear Editorsupporting
confidence: 78%
“…Haploid embryonic stem cells (haESCs) have been recently generated from parthenogenetic (PG) or androgenetic (AG) blastocysts of different mammals, including mouse, rat and monkey, enabling genetic screening at both cellular and organism levels [1][2][3][4][5][6]. However, whether haESCs can be generated from human remains unknown.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…For the WT monkey xenografts, 31 zygotes were generated by ICSI using freeze-thawed sperm (collected 14 months post implantation) with a fertilization rate of ~27.7% (31/112) and then transferred into 12 surrogate female monkeys, resulting in only one pregnancy, which miscarried two months later. To improve the fertilization rate, we applied artificial activation with ionomycin and cycloheximide (CHX) immediately after ICSI [9,10], and obtained a fertilization rate of 76% (38/50). Transferring these 38 zygotes into 12 surrogate females led to one pregnancy that yielded a healthy monkey infant XG7.…”
mentioning
confidence: 99%
“…Recently, a number of studies have derived ESCs from mammalian parthenogenetic and androgenetic haploid embryos. Initial studies were focused on mouse (Elling et al, 2011;Leeb and Wutz, 2011;Li et al, 2012;Yang et al, 2012); however, similar techniques have also been applied to monkey (Yang et al, 2013) and rat haploid ESC derivation . These cell lines have been shown to maintain a haploid karyotype under appropriate culture conditions.…”
Section: Introductionmentioning
confidence: 99%